Erforschung von digitaler Multilokalität zwischen urbanen Zentren und ländlichen Peripherien durch die Kombination und Integration von digitalen und analogen Forschungsmethoden - Bürgin, Reto; Mayer, Heike; Kashev, Alexander; Haug, Sigve (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
The application of mixed methods in researching digitalisation and rural development has numerous benefits in terms of the integration of various data sources. In this paper, we present a novel, mixed methods approach that combines digital and analogue methods. We investigate multilocal work arrangements of knowledge workers in Switzerland who mainly work in a central urban area but occasionally withdraw to peripheral mountain regions in order to conduct their work in a concentrated and undisturbed environment. To analyse such multilocal work arrangements, we use a mixed methods approach that incorporates six integrated methods: geotracking, laptop and smartphone tracking, self-administered digital diaries, ethnographic walk-along observations and qualitative semi-structured interviews. Our study illustrates that mixed methods in digitalisation research provide in-depth insights, but that they also have limitations. Furthermore, we show how ethical standards can and should be used to create a basis of trust with the study participants and how this affects the recruitment of the sample.
Keywords: mixed methods; digital methods; digital multilocality; digitalisation; research ethics; qualitative methods; quantitative methods